Evaluating the temperature inside a tank during a filling with highly-pressurized gas. (21st September 2015) - Bourgeois, Thomas; Ammouri, Fouad; Weber, Mathilde; Knapik, Christophe
Abstract: Gas storage of hydrogen in composite pressure vessels at high pressure is attractive for weight reasons. On the other hand, filling in a short time has to be properly controlled to insure safety. Indeed, compression effects during the H2 fast filling of a cylinder induce a temperature rise inside the gas whose level depends on filling rate, thermal properties of the walls and also geometric characteristics of the cylinder. The effect of each parameter must be well understood to optimize filling quality while maintaining safety. This study presents experimental results obtained on a type IV 90.5 L tank for different filling conditions. Temperatures of the gas have been monitored during filling using temperature sensors. A soft sensor (0D model) has been developed for real time gas temperature estimation during filling. Comparisons between numerical simulations derived from this soft sensor and experimental results are discussed in order to prove the validity of the model and provide a deeper understanding of thermal phenomena in the cylinder. Highlights: We describe experiments of filling o f H2 on a 95 L tank equipped with thermocouples. We build a thermodynamical model of evolution of temperature. We calibrate our model on experiments and study its precision. We find a correlation of heat exchanges between the gas and tank wall.